ANALISIS PEMAHAMAN LITERASI KEUANGAN TERHADAP KINERJA DAN KEBERLANJUTAN UMKM BIDANG F&B DI KOTA TASIKMALAYA - Hasanah, Ade Nurul; Nurbaeti, Nurbaeti; Nirbita, Betanika Nila (Jurnal Ekonomi Manajemen, 2023)
The Small Micro and Medium Enterprises (MSMEs) sector is one of the economic driving sectors that greatly influences the course of the economy in Indonesia. However, as time goes by, there are currently many obstacles in a company's financial literacy, where this financial literacy is very influential in the company's performance and the company's sustainability in the future. The Food and Beverages (FB) sector is a company sector that is still classified as MSMEs which is currently experiencing quite rapid development in several regions in Indonesia, especially in the City of Tasikmalaya. This study aims to determine the impact of the financial literacy knowledge of company owners in the field of Food and Beverages (FB) on the running of companies in Tasikmalaya City. In this study, a literature study method and a qualitative research method were used which were based on the author's experience in observing 2 companies in the field of FB. Based on the research results, it can be concluded that knowledge about financial literacy for a company owner is very important to learn, because a bankruptcy or decreased company income can be affected by the lack of competency of the company owner in carrying out good financial literacy.